RETHINKING AND RE-REMEMBERING PRISON: REIFICATION, AGENCY AND LIMINALITY - Suttner, Raymond (PINS-Psychology in Society, 2025)
This article is both a narrative of my experiences as a political prisoner and a reflection on how this understanding has changed over time. The experiences span a period of forty years, insofar as their impact continues to be part of my psychological being. I relate these encounters within the framework of three main categories. Reification, that is, the attempt by prison authorities to turn prisoners into things, which is apparently, applied in general to common law prisoners. Agency, meaning that the political prisoner or potential prisoner has elements of subjective capacity in varying degrees even in the most adverse conditions, such as undergoing torture. The authorities cannot completely control the political prisoners, or may even cede a great deal to them. Liminality is used to connote the notion of my life being in continuous transition from one state of being, free but potentially in prison, in prison but potentially or definitely to be released, though release is subject to the possibility of re-arrest or other dangers. While the article relates my specific experiences it is intended to signify the capacity of people to choose elements of their existence in other difficult situations.